Urban Gardening Pada Kawasan Hunian Barak Sebagai Upaya Penerapan Edukasi dan Ketahanan Pangan di Kelurahan Bukit Tunggal - Amiany; Ruben Tinting Sirenden; Ave harysakti (Fakultas Teknik Universitas Palangka Raya, 2023)
Bukit Tunggal is one of the densely populated residential areas where there are many barracks, inhabited by many housewives of productive age between 30-46 years old with an average junior high school education who have a lot of free time. Housewives generally take care of the household with a junior high school education without adequate skills. After the pandemic, people tend to be more creative and can be creative to outsmart the existing situation, including in maintaining access to food. People are expected to have the awareness to do independent planting, at least to fulfil their own food needs. There are many ways to do independent planting, such as urban gardening, which is the concept of gardening on limited urban land, which is the right solution for community members, especially housewives, in helping to improve family food security. Therefore, it is necessary to provide knowledge and understanding training to partners so that they are able to master this urban gardening pattern including: (1) preparation, namely preparing training modules, basic knowledge of urban gardening and trials; (2) training implementation: potential vegetables, urban gardening planting methods and media, and direct practice to partners; (3) Partner assistance, and (4) evaluation. The results of vegetable crops that are usually grown include mustard greens, spinach, lettuce, kale, tomatoes and others.